STUDY AND DESIGN OF STREET LIGHTING SYSTEMS USING SOLAR PANEL - Anggara, Fajar; Carles, Henry; Oktaviani, Vira (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
Due to scarcity of fossil fuel, alternative energy has been used upon renewable energy. This research discussed about street lighting plan at PT. Haraka Erfi Kosmetindo Abadi which used solar panels as an alternative energy. The study aims to determine design the capacity of solar panels, batteries and inverters to meet the needs of road lights. The results show that 7 solar panels of 100 Wp are needed, along with 3 units of batteries with a capacity of 100 Ah, 1 unit of PWM type Solar Charge Controller with a capacity of 60 A, and 1 unit of Modified Sine Wave type inverter with a capacity of 500 W. Furthermore, an efficiency of 14.37% was obtained from this system.